Imidazole alkaloids inhibit the pro‐inflammatory mechanisms of human neutrophil and exhibit anti‐inflammatory properties in vivo. (16th January 2019) - Rocha, Talita Magalhães; Machado, Nuno J.; de Sousa, João Antonio Costa; Araujo, Emmanuel Vinicius Oliveira; Guimaraes, Maria Adelaide; Lima, David Fernandes; Leite, José Roberto de Souza de Almeida; Leal, Luzia Kalyne Almeida Moreira
Abstract: Objectives: Epiisopiloturine (EPI) and epiisopilosine (EPIIS) are side products in the pharmaceutical industry. The present study aimed to investigate the anti‐inflammatory potential of the alkaloids EPI and EPIIS in human neutrophils and mechanical hyperalgesia in mice. Methods: Neutrophils (5 × 10 6  cells/ml) incubated with EPI and EPIIS and stimulated by the addition of N‐formyl‐methionyl‐leucyl‐phenylalanine or phorbol 12‐myristate‐13‐acetate. The release of myeloperoxidase (MPO), reactive oxygen species (ROS) production, calcium influx, gene expression of NF‐κB and pro‐inflammatory cytokines production were evaluated. It was also investigated the effect these alkaloids on carrageenan‐induced mechanical hyperalgesia model in mice. Key findings: We demonstrated that both EPI and EPIIS inhibited the degranulation of activated neutrophils. This effect was accompanied by the reduction in ROS, the prevention of the increase in intracellular Ca 2+ and decrease in the density of cytosolic NF‐κB, and inhibition of TNF‐α and IL‐6 production. Evaluating hypernociception in mice, EPI and EPIIS inhibited carrageenan‐induced inflammatory hypernociception and reduced MPO levels. Conclusions: The results obtained suggest EPI and EPIIS not only inhibit neutrophils functions in vitro, but also exhibits anti‐inflammatory properties in vivo, acting through the modulation of the activation and/or accumulation of neutrophils in the inflammatory focus. Thus, EPI and EPIIS possess promising anti‐inflammatory therapeutic potential.